Desafios interdisciplinares da educação para o desenvolvimento sustentável em cursos de administração - Stein, George Ricardo (2010)
The concept of sustainable development refers to the idea that we, humans will be able to continue inhabiting the planet Earth, sharing a well being anchored by conditions socially fair, environmentally sustainable and economically viable. The current state of humanity shows that we are not adopting practices that enable to provide this well-being. This paper addresses the challenges of education for sustainable development (ESD), with specific focus on business management education. Interdisciplinarity is defined and demonstrated as a prerequisite for consideration of the ESD in business management courses, giving the direction to the objective of this research: to investigate the interdisciplinary challenges for EDS in graduate degree in business management. The theoretical reference was consolidated through documental research. The methodology considered the search field characterized by a qualitative approach, developed through forms and semi-structured interviews and observation, conducted on a corporative course, involving students, teachers, supervisors and companies in order to consolidate a number of challenges involving the integrated understanding of different perspectives of the people involved. The results indicate students as the fundamental focus for the course planning, considering them as potential agents for change toward sustainable development. The company that contract graduate courses can be aware and make the direction of the course with this focus, but not releasing the educational institution, where to the main challenges are directed . The institutionalization of education for sustainable development requires not only a review of goals, attitudes and processes, but also a different kind of interaction between managers, teachers and students